<span> (6y^2 + 4y + 5) – (3 – 7y + y^2)
= </span><span> 6y^2 + 4y + 5 – 3 + 7y - y^2
= 5</span>y^2 + 11y + 2
hope it helps
Sounds as tho' you have an isosceles triangle (a triangle with 2 equal sides). If this triangle is also a right triangle (with one 90-degree angle), then the side lengths MUST satisfy the Pythagorean Theorem.
Let's see whether they do.
8^2 + 8^2 = 11^2 ???
64 + 64 = 121? NO. This is not a right triangle.
If you really do have 2 sides that are both of length 8, and you really do have a right triangle, then:
8^2 + 8^2 = d^2, where d=hypotenuse. Then 64+64 = d^2, and
d = sqrt(128) = sqrt(8*16) = 4sqrt(8) = 4*2*sqrt(2) = 8sqrt(2) = 11.3.
11 is close to 11.3, but still, this triangle cannot really have 2 sides of length 8 and one side of length 11.
Answer:
Step-by-step explanation:
In a geometric series, the successive terms differ by a common ratio which is determined by dividing a term by the preceding term.
The formula for determining the nth term of a geometric progression is expressed as
Tn = ar^(n - 1)
Where
a represents the first term of the sequence.
r represents the common ratio between successive terms in the sequence.
n represents the number of terms in the sequence.
From the seies shown,
a = 28
r = 98/28 = 343/98 = 3.5
The formula representing the nth term of the given sequence would be expressed as
Tn = 28 × (3.5)^(n - 1)
Answer:
uttujtjtjtjtjjtjtjtjjttjjtjtjtjtjjt
-3.073 that is the correct answer